Clinical Characteristics of Lamellar Macular Hole Subtypes: Degenerative and Tractional - Joseph Kim; Joon Ki Min; Se Young Kim; Myung Hun Yoon; Hee Seung Chin (Journal of Ophthalmology)
Purpose. To analyze clinical parameters of two subtypes of lamellar macular hole (LMH): degenerative and tractional. Methods. This retrospective chart review study included patients monitored for more than 6 months after the initial diagnosis of LMH from January 2011 to January 2018. LMH was classified in two subtypes: degenerative and tractional. The following parameters between both subtypes were assessed: central subfield thickness (CST), maximum inner diameter (MID), maximum outer diameter (MOD), MID/MOD ratio, inner and outer segment (IS/OS) junction disruption, residual retinal thickness (RRT), subfoveal choroidal thickness (SFCT), best-corrected visual acuity (BCVA), anatomical progression rate, and percentage of patients undergoing surgery. Results. This study included 51 eyes with a mean follow-up period of 18.94 months: 33 eyes with tractional LMH and 18 eyes with degenerative LMH. MID was not significantly different between both subtypes but MOD was significantly greater in tractional LMH than degenerative types (tractional, 1131.6 μm; degenerative, 708.9 μm; p < 0.001). The MID were significantly increased in degenerative eyes, while the tractional eyes featured a significant increase in MOD. BCVA was not significantly different between both subtypes at baseline and the last follow-up. Epiretinal membrane presence was significantly different between the two subtypes (tractional, 96.9%; degenerative, 22.2%; p < 0.001). Ellipsoid defect and rate of receiving surgery were not significantly different between both subtypes. The anatomical progression rate in tractional eyes (81.8%) was significantly higher than that of degenerative LMH (27.7%) (p = 0.010). The SFCT was correlated to anatomical progression in the tractional LMH (correlation coefficient = 0.351, p = 0.049) but not in the degenerative LMH. During the follow-up period, 4 eyes (22.2%) of the degenerative LMH and 11 eyes (33.3%) of the tractional LMH underwent surgery. Conclusions. We found that greater SFCT at baseline was correlated to anatomical progression of tractional LMH. Therefore, it is expected that SFCT could be used as a biomarker to predict anatomical progression in tractional LMH.